2004
DOI: 10.1017/s003329170300878x
|View full text |Cite
|
Sign up to set email alerts
|

Saving clinicians' time by delegating routine aspects of therapy to a computer: a randomized controlled trial in phobia/panic disorder

Abstract: Despite its (non-significantly) higher dropout rate, self-exposure therapy for panic/ phobia cut clinician time per patient by 73% without losing efficacy when guided mainly by a computer rather than entirely by a clinician. The finding needs confirmation at a follow-up that is longer and includes a blind assessor. Self-relaxation had the highest rate of completers but was ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 18 publications
7
165
0
6
Order By: Relevance
“…Only eight reported allocation to conditions by an independent party. Blinding of assessors was reported in seven studies (Bornas, TortellaFeliu, & Llabrés, 2006;Carlbring et al, 2005Carlbring et al, , 2006Ghosh et al, 1988;Greist et al, 2002;Marks et al, 2004). Dropout ranged from 2 to 29% (two studies did not report dropout; Bornas, Tortella-Feliu, Llabrés, & Fullana, 2001;Hassan, 1992).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Only eight reported allocation to conditions by an independent party. Blinding of assessors was reported in seven studies (Bornas, TortellaFeliu, & Llabrés, 2006;Carlbring et al, 2005Carlbring et al, , 2006Ghosh et al, 1988;Greist et al, 2002;Marks et al, 2004). Dropout ranged from 2 to 29% (two studies did not report dropout; Bornas, Tortella-Feliu, Llabrés, & Fullana, 2001;Hassan, 1992).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…Dropout ranged from 2 to 29% (two studies did not report dropout; Bornas, Tortella-Feliu, Llabrés, & Fullana, 2001;Hassan, 1992). In 11 studies Carlbring, Ekselius, & Andersson, 2003;Carlbring, Westling, Ljungstrand, Ekselius, & Andersson, 2001;Carlbring et al, 2005Carlbring et al, , 2007Greist et al, 2002;Kenardy et al, 2003;Knaevelsrud et al, 2007;Marks et al, 2004; Note. CAVE5computer-aided vicarious exposure; CAFFT5computer-assisted fear of flying treatment; CBSM5computer-based symbolic modeling; NR5not reported; SHTC5self-help program for traumatic event-related consequences; SBT5cognitive behavioural therapy; PTSD5posttraumatic stress disorder; OCD5obsessive-compulsive disorder; FTF5face to face; IVR5interactive voice response.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Marks et al, (2004), a computer-aided CBT (CCBT) is described for delivering selfhelp for sufferers with phobic, panic, anxiety, obsessive-compulsive and depressive disorders. Although the approach greatly reduced the demand on therapist's time, it lacked the patient -doctor feedback mechanism which is crucial for depression therapy.…”
Section: Related Workmentioning
confidence: 99%
“…These treatment approaches include guided relaxation, instructionalbased self-exposure (Marks, Kenwright, McDonough, Whittaker, & Mataix-Cols, 2004), vicarious exposure (Gilroy, Kirkby, Daniels, Menzies, & Montgomery, 2003), virtual reality (Krijn, Emmelkamp, Olafsson, & Biemond, 2004) and symbolic exposure via images and videos (Bornas et al, 2002;Matthews, Scanlan, & Kirkby, 2012;Vansteenwegen et al, 2007). A recent metaanalysis concluded that exposure-based interventions were more effective than placebo, or alternative psychotherapeutic interventions, and that in vivo exposure (involving direct contact with the phobic stimulus) was more effective than 'other' exposure-based interventions (e.g., imaginal, virtual reality) at post-treatment but not at follow-up (Wolitzky-Taylor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%